Foundations and practice of security : 12th International Symposium, FPS 2019, Toulouse, France, November 5-7, 2019, Revised selected papers /: 12th International Symposium, FPS 2019, Toulouse, France, November 5-7, 2019, Revised selected papers. (2020) - Unknown
No abstract available